Improving Children's Education through the Tutoring Program at Sentul Malaysia Kuala Lumpur Tutoring Studio - Nabila Fitriyani; Yasir Sidiq; Ganno Tribuana Aji; Muhammad Nizar; Muhammad Samsuri; Sri Sat Titi Hamranani (Asosiasi Lembaga Pendidikan Tenaga Kependidikan Peguruan Tinggi Muhammadiyah dan Aisyiyah, 2023)
Education is something very important that needs to be guided for children. Learning guidance strongly supports the crucial development of children's learning because it is not only available within the school system. The existence of this learning guidance program can enhance quality educational services for children. In education, students are encouraged to learn through various methods. This activity is more relaxed compared to other forms of education. All students are not forced to memorize only but they must understand and be interested in what we teach because learning is more enjoyable when using interactive methods. Educational services can also be interpreted as educational services. The word